Perubahan Parameter Parameter Marshal Akibat Perbedaan Jumlah Tumbukan pada Aspal Concrete – Wearing Course (ACWC) Gradasi Halus - Istanto, Teguh Dwi; Pratomo, Priyo; Ali, Hadi (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2015)
This study was conducted to see the changes in the value of the parameter values marshall afterthe number of collisions in the standards vary the amount of the collision then analyzed thenumber of collision and then analyzed the number of collisions are most effective assessed on thevalue of the characteristic marshall. In the Marshall planning standard for the number ofcollisions of heavy traffic conditions compaction test specimen as 2x75 collision with a mixturecavity boundary between 3.5-5%.This study uses gradation Asphalt Concrete - Wearing Course (AC-WC) smooth gradations formiddle and upper limits. From the data obtained aggregate gradation and asphalt aggregatedemand needs are used to find the optimum bitumen content that is used in the manufacture of testspecimens for variations in the number of collisions is 2x55, 2x65, 2x75, 2x85, and 2x95. Marshallthen test to see the number of collisions are most effective against the characteristics of asphaltmixture.Based on the analysis of the data processing is obtained that the value content of asphalt is used tolimit the middle that is 5.7% and the upper limit of 6.5%. Total Collision 2x75 and 2x85 that meetsall the parameters marshall. For the number of collisions 2x55 and 2x65 obtained small stability,voids In The Mix (VIM) is great and does not make the specification, to the number of collisions2x95, obtained great stability and voids In The Mix (VIM) is small and does not get in thespecification.Keywords: Collision, Marshall, Asphalt Concrete - Wearing Course (AC-WC), Smooth Gradation